Three-Dimensional Morphology Study of Capsule in Pseudophakic Eyes with High-Speed Swept-Source Optical Coherence Tomography. (3rd June 2019) - Xixia, Ding; Pingjun, Chang; Hongfang, Zhang; Giacomo, Savini; Jinhai, Huang; Feixue, Chu; A-yong, Yu; Fang, Huang; Shenghai, Huang; Lei, Lin; Yun-e, Zhao
ABSTRACT: Purpose: To study the capsule morphology in pseudophakic eyes on the three-dimensional level using high-speed swept-source optical coherence tomography (SSOCT). Methods: This study collected patients with age-related cataract and divided them into two groups according to the anterior capsule and intraocular lens (IOL) optic relationship: total anterior capsule overlap (360°, Group-T) and partial anterior capsule overlap (<360°, Group-P). One standard SSOCT radial scanning was performed in all eyes at 1 day, 1 week, 1 month, and 3 months postoperatively. Results: Thirty-two eyes from 25 patients were enrolled in the Group-T and 17 eyes from 13 patients in the Group-P. No eyes achieved complete adhesion between IOL optic and posterior capsule at 1 day after the surgery. However, the rate of complete adhesion was low (15/49, 30.6%) even at 3 months postoperatively and there was no statistically difference between Group-T and Group-P (21.9% vs. 47.1%, P > 0.05). At 1 day, 1 week, 1 month, and 3 months after the surgery, the capsule bend index (CBI) in the Group-T was 0.02 ± 0.09, 1.35 ± 1.48, 3.60 ± 0.54, and 3.88 ± 0.19, respectively. CBI rises linearly during the first month and the rise goes stable relatively with the great reduction of standard deviation in the following 2 months (All P < 0.05). The anterior capsule opening area and diameter were both reduced in the first month, and then they both became stable. Conclusions: With square-edge IOL, posterior capsule opacification risk is still high in most eyes at 3 months postoperatively for the complete adhesion of posterior capsule and IOL was only achieved in 30.6% eyes. IOL-in-bag may be driven by the significant capsule bag changes especially in the first month postoperatively.